Ambient air pollution exposed during preantral-antral follicle transition stage was sensitive to associate with clinical pregnancy for women receiving IVF. (October 2020) - Li, Lipeng; Zhou, Lixiao; Feng, Tengfei; Hao, Guimin; Yang, Sujuan; Wang, Ning; Yan, Lina; Pang, Yaxian; Niu, Yujie; Zhang, Rong
Abstract: Maternal exposure to air pollution is associated with poor reproductive outcomes in in vitro fertilization (IVF). However, the susceptible time windows are still not been known clearly. In the present study, we linked the air pollution data with the information of 9001 women receiving 10, 467 transfer cycles from August 2014 to August 2019 in The Second Hospital of Hebei Medical University, Shijiazhuang City, China. Maternal exposure was presented as individual average daily concentrations of PM2.5, PM10, NO2, SO2, CO, and O3, which were predicted by spatiotemporal kriging model based on residential addresses. Exposure windows were divided to five periods according to the process of follicular and embryonic development in IVF. Generalized estimating equation model was used to evaluate adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for association between clinical pregnancy and interquartile range increased average daily concentrations of pollutants during each exposure period. The increased PM2.5 (adjusted OR = 0.95, 95% CI: 0.90, 0.99), PM10 (adjusted OR = 0.93, 95% CI: 0.89, 0.98), NO2 (adjusted OR = 0.89, 95% CI: 0.85, 0.94), SO2 (OR = 0.94, 95% CI: 0.90, 0.98), CO (adjusted OR = 0.93, 95% CI: 0.89, 0.97) whereas decreased O3 (OR = 1.08, 95% CI: 1.02, 1.14) during the duration from preantral follicles to antral follicles were the strongest association with decreased probability of clinical pregnancy among the five periods. Especially, women aged 20–29 years old were more susceptible in preantral-antral follicle transition stage. Women aged 36–47 years old were more vulnerable during post-oocyte retrieve period. Our results suggested air pollution exposure during preantral-antral follicle transition stage was a note-worthy challenge to conceive among females receiving IVF. Graphical abstract: Image 1 Highlights: Air pollution was associated with clinical pregnancy in in vitro fertilization. Preantral-antral follicle transition stage was critical response to air pollution. Women aged 20–29 were more vulnerable in preantral-antral follicle transition stage. Women aged 36–47 were more susceptible after oocyte retrieved. Abstract : Capsule: Women exposed to ambient air pollution during preantral-antral follicle transition stage was a critical time-window associated with clinical pregnancy in in vitro fertilization.